2017
DOI: 10.1371/journal.pone.0188670
|View full text |Cite
|
Sign up to set email alerts
|

Site-level progression of periodontal disease during a follow-up period

Abstract: Periodontal disease is assessed and its progression is determined via observations on a site-by-site basis. Periodontal data are complex and structured in multiple levels; thus, applying a summary statistical approach (i.e., the mean) for site-level evaluations results in loss of information. Previous studies have shown the availability of mixed effects modeling. However, clinically beneficial information on the progression of periodontal disease during the follow-up period is not available.We conducted a mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 48 publications
0
37
1
Order By: Relevance
“…Also, our findings that there were increased amount of total bacteria and increased percentage of red complex bacteria (Pg, Td, or Tf) in disease and DP sites unrelated to EBV contrast with the suggestion that EBV is a cofactor in periodontal disease (Contreras & Slots, 2001;Contreras, Umeda, et al, 1999;Contreras, Zadeh, Nowzari, & Slots, 1999;Kato, Imai, Ochiai, & Ogata, 2015;Slots, 2007 when treatment is not provided (Kocher, Konig, Dzierzon, Sawaf, & Plagmann, 2000;Nomura et al, 2017;Ramseier et al, 2017). Further, our findings suggest that the standard of care is effective for most sites (i.e.…”
Section: Discussioncontrasting
confidence: 58%
See 2 more Smart Citations
“…Also, our findings that there were increased amount of total bacteria and increased percentage of red complex bacteria (Pg, Td, or Tf) in disease and DP sites unrelated to EBV contrast with the suggestion that EBV is a cofactor in periodontal disease (Contreras & Slots, 2001;Contreras, Umeda, et al, 1999;Contreras, Zadeh, Nowzari, & Slots, 1999;Kato, Imai, Ochiai, & Ogata, 2015;Slots, 2007 when treatment is not provided (Kocher, Konig, Dzierzon, Sawaf, & Plagmann, 2000;Nomura et al, 2017;Ramseier et al, 2017). Further, our findings suggest that the standard of care is effective for most sites (i.e.…”
Section: Discussioncontrasting
confidence: 58%
“…Further, more needs to be done to identify the risk factors involved in disease progression, and how best to prevent disease progression. As practitioners target more precise therapies, it is important to realize that Pg, Td, and Tf are strongly associated with disease progression as documented by our findings and many others (Farias et al, 2012;Nomura et al, 2017;Teles et al, 2008); thus, these periodontal pathogens should be targeted for elimination, if progression of periodontitis is to be halted.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…When tooth-level analysis is carried out, each tooth is not statistically independent, as each tooth is nested in a subject’s and tooth’s constructed hierarchy structure. The mixed-effect model was used to calculate the sensitivity for dental caries at the tooth level [ 39 , 40 ]. Sex and age were used for the subject-level parameter, and with or without dental caries by tooth was used for the tooth-levels parameter.…”
Section: Methodsmentioning
confidence: 99%
“…actinomycetemcomitans in saliva were significantly related to the progression of periodontitis during periodontal maintenance (Morozumi et al, 2016;Nomura et al, 2012Nomura et al, , 2017). In the current study, P. gingivalis, P. intermedia, A. actinomycetemcomitans and T. forsythia in saliva at baseline were analysed; we found that the detection of A. actinomycetemcomitans increased the probability of further attachment loss in the multivariate model, while, surprisingly, a lower T. forsythia load was associated with a higher probability of further attachment loss in both univariate and multivariate models.…”
Section: F I G U R Ementioning
confidence: 99%